Answer:
(a) [tex]v = \sqrt{ mv_0^2 - 2gL(1-\cos(\theta))}[/tex]
(b) [tex]\theta = \arccos(\frac{2gL-v_0^2}{2gL})[/tex]
(c) [tex] E_{total} = \frac{1}{2}mv_0^2[/tex]
Explanation:
(a) The total mechanical energy of the system is conserved.
[tex]K_A + U_A = K_B + U_B\\\frac{1}{2}mv_0^2 + 0 = \frac{1}{2}mv^2 + mgh \\h = L - L\cos(\theta) = L(1 - \cos\theta)\\\frac{1}{2}mv^2 = \frac{1}{2}mv_0^2 - mgL(1-\cos(\theta))\\v^2 = mv_0^2 - 2gL(1-\cos(\theta))\\v = \sqrt{ mv_0^2 - 2gL(1-\cos(\theta))}[/tex]
(b) The conservation of energy states
[tex]K_A + U_A = K_M + U_M\\\frac{1}{2}mv_0^2 + 0 = 0 + mgL(1-\cos(\theta))\\1-\cos(\theta) = \frac{v_0^2}{2gL}\\\cos(\theta) = 1-\frac{v_0^2}{2gL} = \frac{2gL-v_0^2}{2gL}\\\theta = \arccos(\frac{2gL-v_0^2}{2gL})[/tex]
(c) As explained in part (a) the total mechanical energy of the system is equal to the initial kinetic energy, since the potential energy of the system at that point is zero.
[tex]E_{total}= K_A + U_A = K_A + 0\\E_{total} = \frac{1}{2}mv_0^2[/tex]